2019
DOI: 10.1039/c8ra09887e
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach coupling ferrous iron bio-oxidation and ferric iron chemo-reduction to promote biomineralization in simulated acidic mine drainage

Abstract: Controlled addition of ZVI into Acidithiobacillus ferrooxidans-mediated biomineralization can markedly improve the formation of secondary Fe-minerals in AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Briefly, 80 mM FeSO 4 solution (250 mL) was inoculated with A. ferrooxidans resting cell (6 × 10 7 cells mL –1 ) and co-cultured for 5 days at an initial pH of 2.5 and 180 rpm (28 °C). , At a given time interval, 2 mL of suspension was withdrawn and determined for pH, Fe 2+ , total Fe, and SO 4 2– after filtering through a 0.45 μm membrane. The resultant precipitate was collected by vacuum filtration and then washed three times with H 2 SO 4 solution (pH = 2.0) and deionized water, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 80 mM FeSO 4 solution (250 mL) was inoculated with A. ferrooxidans resting cell (6 × 10 7 cells mL –1 ) and co-cultured for 5 days at an initial pH of 2.5 and 180 rpm (28 °C). , At a given time interval, 2 mL of suspension was withdrawn and determined for pH, Fe 2+ , total Fe, and SO 4 2– after filtering through a 0.45 μm membrane. The resultant precipitate was collected by vacuum filtration and then washed three times with H 2 SO 4 solution (pH = 2.0) and deionized water, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Jarosite is able to synthesize in the presence of some ions including Cr(III), Hg(II), Pb(II) under certain temperature and pH in solution, since it is insoluble in a dilute acid environment and easy to precipitate (Daoud et al 2006). The synthesis rate of jarosite catalyzed by A. ferrooxidans (increase in the oxidation rate of Fe(II)) was found to be faster than that by chemical synthesis (Wang et al 2019;Guay et al 1977). It has been documented that the biosynthesized jarosite has some specific traits such as uniform dispersive crystal structure and smooth profile (Henao et al 2010).…”
Section: Jarositementioning
confidence: 97%
“…It has been reported that schwertmannite synthesized by A. ferrooxidans can degrade methyl orange (Zhang et al 2018). The biosynthetic schwertmannite can exhibit a high catalytic efficiency at a neutral environment with a pH of 7.5, which can overcome the disadvantage of a narrow pH range for a homogeneous fenton reaction (Wang et al 2019). The catalytic degradation of methyl orange by biosynthetic schwertmannite can still be carried out under a high concentration of nitrate, sulfuric acid and chloride ions (Xiang Li et al 2018).…”
Section: Application Of Schwertmannitementioning
confidence: 99%
See 1 more Smart Citation
“…With the highly enantiopure α‐chloroaldehyde in hand, we next turned our attention to the diastereoselective addition of organometallic reagents . For the optimization of this step we used the non‐branched building block that results in (+)‐monachalure (+)‐ 1a (Scheme ).…”
Section: Resultsmentioning
confidence: 99%